Removing the straight jacket in practice approach: An investigation into coach learning and development in Australian female tennis - Moulds, K.; Lascu, A.; Bai, A.; Davidson, J. (International Journal of Sports Science and Coaching, 2025)
Objectives Applying an ecological dynamics perspective with the Skilled Intentionality Framework, this study examined whether an integrated coach learning and development framework could be successfully implemented in Australian female tennis coaching.